High molecular weight kininogen contributes to early mortality and kidney dysfunction in a mouse model of sickle cell disease. (27th August 2020) - Sparkenbaugh, Erica M.; Kasztan, Malgorzata; Henderson, Michael W.; Ellsworth, Patrick; Davis, Parker Ross; Wilson, Kathryn J.; Reeves, Brandi; Key, Nigel S.; Strickland, Sidney; McCrae, Keith; Pollock, David M.; Pawlinski, Rafal
Abstract: Background: Sickle cell disease (SCD) is characterized by chronic hemolytic anemia, vaso‐occlusive crises, chronic inflammation, and activation of coagulation. The clinical complications such as painful crisis, stroke, pulmonary hypertension, nephropathy and venous thromboembolism lead to cumulative organ damage and premature death. High molecular weight kininogen (HK) is a central cofactor for the kallikrein‐kinin and intrinsic coagulation pathways, which contributes to both coagulation and inflammation. Objective: We hypothesize that HK contributes to the hypercoagulable and pro‐inflammatory state that causes end‐organ damage and early mortality in sickle mice. Methods: We evaluated the role of HK in the Townes mouse model of SCD. Results/Conclusions: We found elevated plasma levels of cleaved HK in sickle patients compared to healthy controls, suggesting ongoing HK activation in SCD. We used bone marrow transplantation to generate wild type and sickle cell mice on a HK‐deficient background. We found that short‐term HK deficiency attenuated thrombin generation and inflammation in sickle mice at steady state, which was independent of bradykinin signaling. Moreover, long‐term HK deficiency attenuates kidney injury, reduces chronic inflammation, and ultimately improves survival of sickle mice.